KAJIAN PEMANFAATAN SUMBER DAYA MAMALIA LAUT DI KEPULAUAN BERAU, KAUMANTAN TIMUR (Assessment of Cetacean Resources Utilization in Berau Islands, East Kalimantan) - Budy Wiryawan; Benjamin Kahn (Institut Pertanian Bogor, 2007)
This paper will explain the result of cetacean reconaissance survey including investigation of abundance and diversity of cetacean related to the designing of a co management Marine Protected Area (MPA) in Berau, East Kalimantan. Berau islands consist of 31 very small islands that have high marine biodiversity including mangrove, coral reefs, sea grass. It has been found by this survey that Berau waters is a corridor for cetacean migration route, beside as home for green turtles and manta ray aggregation sites in Indonesia. This reconaisance survey in the frame oj Rapid Ecological Assessment using visual and acoustic method, indicated that cetacean existence is closely related to the coral reef ecosystem and small islands. Berau islands is an integral part of 'Coral Triangle' within marine mega biodiversity area, and it is inhabited by at least 10 species ofcetacean.Conservation of marine cetacean in the frame work of MPA will ensuresustainable marine resource use, including tourism and fisheries, for the benefit of local communities. The strategies pursuant to this goal will be arrived upon through the linkage of partnerships that have been created, and the objective will be achieved by establishing a large, co-managed Marine Protected Area that will include extractive use zones, non-extractive use zones and fully protected (no-take) zones. Partnership amongstgauernment and NGOs has already been innitiated in Berau. Currently the MPA boundary covers an area of 1.2 million Hectars of Berau waters, including corridor of cetacean migration, that has been formalized through District Decree No.31/2005.Keywords: Marine Protected Area, Rapid Ecological Assessment, Marine Cetacean.